Application of Time-Varying Mortality Rate Model in Pension System: A case of Tanzania - Suleiman, Samya; Andongwisye, John; Sinkwembe, Emmanuel E.; Lundengård, Karl (Tanzania Journal of Science, 2024)
The current increase in the ageing population, driven by a decrease in mortality rates, has impacted most pay-as-you-go defined benefit pension schemes. The resulting increase in the dependency ratio places a greater burden on these schemes. Many pension funds currently use static lifetables to project future obligations, overlooking the gradual decline in mortality rates. This study explores the application of a time-varying mortality rate model to forecast Tanzanian mortality rates. The time-varying model was successfully employed together with multi state method to project and analyse the funding ratio and cashflow to asset value ratio of the mandatory Tanzania Public Service Social Security Fund for the years 2020–2070. Numerical results indicate a decreasing trend in mortality rates over time, leading to a decline in the funding ratio from 92.92% in 2020 to 21.12% in 2070. Additionally, a decrease in cash flow will result in a 0.25% depletion of assets by 2060. Therefore time-varying mortality rate model is an effective tool for pension systems to forecast mortality rates and project their future financial obligations.